High rate of extreme thrombocytosis indicates bone marrow hyperactivity and splenic dysfunction among congenital diaphragmatic hernia patients. (4th July 2022) - Gu, Hannah; Devine, Matthew; Hedrick, Holly L.; Rintoul, Natalie E.; Thom, Christopher S.
Abstract: Pediatric extreme thrombocytosis (EXT, platelet count > 1000 x 10 3 /µL) is rare. In a single center retrospective analysis of hospitalized children with EXT, infants with congenital diaphragmatic hernia (CDH) were overrepresented. In general pediatric patients, EXT is usually secondary to infection or inflammation, but most of the 14 CDH patients with EXT had no identifiable inciting factor. Instead, there was evidence that splenic dysfunction and bone marrow hyperactivity underlied EXT in CDH patients. None were associated with bleeding or thrombosis. Our findings identify mechanisms underlying EXT, and aid clinical interpretation and management of EXT in the pediatric population.